Managing dynamic business environments: India's future automotive industry. Issue 4 (11th November 2014) - Kuklinski, Christian; Moser, Roger; Callarman, Thomas
Abstract : Purpose: – This paper aims to examine from an information processing perspective how Delphi-based analyses can be used to overcome some challenges of dynamic business environments in emerging markets. Design/methodology/approach: – Delphi-based, future-oriented approach utilizing scenario planning methodology based on real-time expert-panel data. Findings: – Delphi-based analyses can indeed serve as an information processing aid to reduce uncertainty and equivocality in an emerging market. Originality/value: – A multistage analysis approach integrating the political, economic, socio-cultural and technological-stakeholder framework to support and better structure managers' information processing in an emerging market.